Concomitant Administration of Capecitabine and Folate Supplements: Need to Encourage Medication Reconciliation - Berenice Stefanelli; Carmine Sellitto; Emanuela De Bellis; Martina Torsiello; Nicola Bertini; Angelo Maria Pezzullo; Graziamaria Corbi; Francesco Sabbatino; Stefano Pepe; Angela Tesse; Valeria Conti; Amelia Filippelli (MDPI AG, 2022)
Hand-Foot syndrome (HFS) and diarrhoea are dose-limiting Adverse Drug Reactions (ADRs) of capecitabine-based chemotherapy. Four polymorphisms in the dihydropyrimidine dehydrogenase (DPYD) gene, encoding the DPD enzyme responsible for the metabolism of fluoropyrimidines, such as capecitabine, are strongly associated with severe ADRs, and their screening should be performed before starting treatment. Moreover, capecitabine-related toxicity may worsen due to drug-drug and drug-supplement interactions. Here we investigated factors responsible for severe HFS and diarrhoea presented by two patients, non-carriers of the recommended DPYD single nucleotide polymorphisms (SNPs) but carriers of other genetic variants suggested to increase the risk of capecitabine-related ADRs. Through careful therapy recognition, we demonstrated that, unbeknownst to the oncologists, the patients were taking folic acid during the treatment with capecitabine at a dosage higher than 2000 mg/m2, which is the maximum tolerated dose when folate is administered. To resolve the ADRs, the therapy had to be drastically changed. In one case, dose reduction of capecitabine and discontinuation of lipid-lowering agents were carried out. In the other case, discontinuation of capecitabine and folic acid and capecitabine re-administration were performed after a month. Genetic and environmental factors should be considered good predictors of severe capecitabine-related toxicity. Medication reconciliation should be encouraged to avoid the harmful consequences of inappropriate treatments.